UNPACKING CODE MIXING IN ENGLISH SPEAKING: A CASE STUDY ON GENERATION Z LEARNERS - Reno Julyan; Dwi Nopiyadi; Utami Rosalina (NextGen Education Review Journal, 2025)
This research unpacks the phenomenon of code mixing among Generation Z students and its repercussion on English speaking skills. Using a qualitative descriptive case study, the study was conducted with second-semester English education students at Prima Bangsa Institute, Cirebon. Data were collected through classroom observation and interviews, both directly and via online forms, to capture authentic communication. The analysis applies Soewito’s (1985) and Callhavid’s (2010) theory of code mixing types, including word, phrase, reduplication, hybrid, idiom, and clause insertion, as well as Hoffman’s (1991) theory of functions such as expressing topics, empathy, interjections, clarification, group identity, and quoting others. The results show that students frequently mix Indonesian and English, influenced by digital culture and social media, to communicate more flexibly and naturally. Furthermore, code mixing supports their speaking development by expanding vocabulary, improving pronunciation, enhancing comprehension, and boosting confidence.